Green Corrosion Inhibitors to Head Off the Corrosion Rate of ST 37 Steels - Devi Eka Septiyani Arifin; Destri Muliastri; Rudi Rudiana; Fitri Nur Indah Sari (Bandung State Polytechnic (Politeknik Negeri Bandung), 2021)
The corrosions process is a natural process and cannot be hindered, but it can be protected by adding a green inhibitor. Green corrosion inhibitors are a new alternative solution for corrosion protection because they are low-cost, biodegradable, and eco-friendly inhibitors. This research was used papaya leaves dan guava leaves extract as organic inhibitor solution by Maceration Method. The concentration of these green inhibitors is 0 mL, 1 mL, 2.5 mL, 3 mL, and 3.5 mL. The type of testing method used in this research is FTIR, PDP, and weight loss. The results show that there is Tanin function groups in papaya leaves and guava leaves extract. The potentiodynamic polarization shows the value of corrosion rate without inhibitor is 0,418 mm/year. In contrast, the corrosion rate was decreased with improving the green inhibitor as many 3.5 mL. The corrosion rate was decreased until 0,00055 mm/year, and the value of efficiency is 99,868%.